PROSES PEMBEKUAN FILLET IKAN ANGGOLI BENTUK SKIN ON DI CV. BEE JAY SEAFOODS PROBOLINGGO JAWA TIMUR - Lovi Sandra; Husnur Riayah (Faculty of Science and Technology University Ibrahimy, 2015)
The purpose of this study was to determine the direct range of the freezing process Anggoli fish fillet products (Pristipomoides multidens) in the shape of skin on (SKO) held at Jay Bee Seafoods CV Probolinggo, East Java. The research was conducted in January to April 2014. The method used in this research is the survey method, the primary data is taken through observation, interviews, documentation and direct participation in the field. Secondary data was collected through literature. The data were analyzed descriptively. Fish freezing process Anggoli (p.multidens) in the form of skin on (SKO) carried out in CV Bee Jay Probolinggo include the following stages: 1) Acceptance of raw materials; 2) sorting I; 3) weighing I; 4) shelter; 5) cleaning the fish scales; 6) washing II; 7) the fillet; 8) the lifting of thorns; 9) trimming; 10) sorting of products; 11) washing III; 12) packaging and vacuum process; 13) freezing, 14) detection products, 15) packing; 16) storage; and 16) export. Raw materials in fish fillet products Anggoli form of skin on Cv. Jay Bee Seafoods in the form of fresh, whereas the auxiliary materials used are water and ice.